Inhibition of mitochondrial division through covalent modification of Drp1 protein by 15 Deoxy- Δ(12,14) - Prostaglandin J(2) - Mishra, Nandita (2010)
Arachidonic acid derived endogenous electrophile 15d-PGJ2 has gained much attention in recent years due to its potent anti-proliferative and anti-inflammatory actions mediated through thiol modification of cysteine residues in its target proteins. Here, we show that 15d-PGJ2 at 1µM concentration converts normal mitochondria into large elongated and interconnected mitochondria through direct binding to mitochondrial fission protein Drp1 and partial inhibition of its GTPase activity. Mitochondrial elongation induced by 15d-PGJ2 is accompanied by increased assembly of Drp1 into large oligomeric complexes through plausible intermolecular interactions. The role of decreased GTPase activity of Drp1 in the formation of large oligomeric complexes is evident when Drp1 is incubated with a non-cleavable GTP analog, GTPγS or by a mutation that inactivated GTPase activity of Drp1 (K38A). The mutation of cysteine residue (Cys644) in the GTPase effector domain, a reported target for modification by reactive electrophiles, to alanine mimicked K38A mutation induced Drp1 oligomerization and mitochondrial elongation, suggesting the importance of cysteine in GED to regulate the GTPase activity and mitochondrial morphology. Interestingly, treatment of K38A and C644A mutants with 15d-PGJ2 resulted in super oligomerization of both mutant Drp1s indicating that 15d-PGJ2 may further stabilize Drp1 oligomers formed by loss of GTPase activity through covalent modification of middle domain cysteine residues. The present study documents for the first time the regulation of a mitochondrial fission activity by a prostaglandin, which will provide clues for understanding the pathological and physiological consequences of accumulation of reactive electrophiles during oxidative stress, inflammation and degeneration.